Medical Treatment of Postendoscopic Submucosal Dissection Phlegmonous Gastritis in an Elderly Diabetic Woman with Myelodysplastic Syndrome. (30th September 2018) - Matsuura, Ko; Hiramatsu, Shinsuke; Taketani, Rika; Ishibashi, Kohei; Uraoka, Masanao; Baba, Shinichi; Nakamura, Akihiro; Takihara, Hiroshi; Ueda, Chie; Inoue, Taro
Abstract : Phlegmonous gastritis is a rare, suppurative disease characterized by full-thickness exudative changes, infiltration of inflammatory cells, and edema primarily in the submucosal layer. A 76-year-old woman with type 2 diabetes and myelodysplastic syndrome underwent endoscopic submucosal dissection (ESD) for early gastric cancer. Postoperatively, she developed persistent fever and computed tomography displayed full-circumference thickening of the gastric wall and increased levels of fat stranding. Endoscopy showed post-ESD ulcer floor expansion, formation of a false lumen between the ulcer floor and surrounding folds, and adhesion of purulent matter. Klebsiella pneumoniae, Pseudomonas aeruginosa, and Candida albicans were detected from pus culture and Klebsiella pneumoniae from blood culture, leading to a diagnosis of phlegmonous gastritis. Contrast examination showed no leakage outside the gastric wall; therefore, the patient fasted and was given antibiotics. She was successfully treated with medical therapy, as demonstrated by repeat endoscopy. Based on our experience, we recommend antibiotics before and after ESD in patients thought to be at high risk of infection, as well as careful postoperative management including postoperative endoscopy.